Litter Decomposition and Nutrient Release Pattern of Some Prominent Tree Species in The Cool-Temperate Forests of the Nanda Devi Biosphere Reserve in Uttarakhand, India - Shankar Datt TIWARI (International Journal of Conservation Science, 2013)
The present study was conducted in the buffer zone of the Nanda Devi Biosphere Reserve, which is situated in the Himalayan highlands, biogeographic province-2B in India. The area is completely protected since January 7th, 1939, when it was declared as a sanctuary. Now it has been included in the list of ‘World Heritage Sites’, since 1992. The area is reputedly one of the most spectacular wildernesses having qualitatively as well as quantitatively a unique biota, cultural heritage, religious faith, climate and soil type in the world. Geographically it falls between 30017’N to 30041’N latitude and 79040’E to 80005’E longitude and makes headwaters of Dhauliganga and Rishiganga, tributaries of the National river Ganga, in Uttarakhand. The parent material mainly represents crystalline rocks and comprises garnetiferous mica, schists, garnet mica and mica quartzite. The soil under broad-leaved forests is usually dark black and deep due to the decomposition of a large amount of accumulated organic matter, while under coniferous forests, it is generally light and shallow, due to the presence of hard rocks in soils and a smaller amount of organic matter. Out of the 10 identified species and their composition,, the moisture holding capacity of litter observed in composite leaf litter (19.73%) was the highest and in the Cedrus leaf litter (8.20% )the lowest. The turnover rate (r) ranged from 0.61 in Cedrus leaves to 0.74 in A. caesium, J. regia and Q. semecarpifolia leaf litter. The turnover time (t) was lowest for J. regia and A. caesium (1.35) and highest for the Cedrus leaf litter (1.65).